Human-Robot Symbiosis:Our Desire to Renovate Practical Learning Sciences by Introducing Robots - Miyake, Naomi (Cognitive Studies: Bulletin of the Japanese Cognitive Science Society, 2012)
The aim of this short article is to explore new trends of studying learning practices in reality, in order to ultimately raise their quality. By having accumulated huge amount of “learning” studies, we now have a rich data-base of “rules of thumb” to promote education. In order to raise the adaptive generalize-ability of such rules, we explore the use of remotely operable robots, by having them play the role of a learning partner as a good listener in constructive interaction that occurs in collaborative classrooms. This allows us, for the first time in our study, to quasi-control different groups of collaboration byintroducing “same” activities only playable by such robots. Their roles as listener also actualize an important function to collect more detailed and desired process data from learner-centered classrooms, which has been practically almostimpossible to collect. To approach these aims, our joint project named “Human-Robot Symbiosis” has been exploring new challenges on robotics engineering,cognitive science of human-robot relation setting, and on understanding and implementing basic mechanisms of collaborative learning. The article demonstrates three new types of study in the third topic. One is on using a series of class-room like Lego-block building class run by a robot to promote spontaneous collaboration among children. Another is on confirming perspective expansion effects to promote spontaneous dialoguing to appreciate art works, by having a robot participate in the dialogue to provide a “new” perspective into it by the highly experienced operators. The other is on identifying effective roles of learning partnersin collaborative classes carefully designed to promote constructive interaction for integration of knowledge. All show the importance of giving learning agency to learners in different situations. It concludes with directions for futurestudy.